Local Governance in Western Europe - Peter John (SAGE Publications Ltd, 2001)
This book arose from a course, Comparative Local Government and Urban Politics, which I taught with Keith Dowding at the London School of Economics between 1997 and 2000. Students on the Public Administration and Public Policy and Regional and Urban Planning masters’ degrees could take it as an option. The long title of the course reflected a dialogue between the traditions of urban political science, on the one hand, and comparative local government studies on the other. The study of urban politics originates in the United States of America and focuses on power and policy-making in cities. Scholars take the context of urban politics as the important determinant of decision-making, particularly the exigencies of the economy. They examine individual and group choices within the urban setting, covering topics like the power of local elites, the demands of the business sector and competition between urban centres. As well as carrying out empirical studies, urbanists privilege social science theory, acknowledging debates on pluralism, elitism, Marxism and rational choice theory (for a review, see Judge et al., 1995). In contrast, comparative local government studies is a branch of the study of public administration, mainly concentrating on elected local governments in Western Europe and the English-speaking world. Researchers wish to understand the operation of political institutions, in particular the significance of legal frameworks, the allocation of functions between tiers of government and the impact of the size of local government units. Topics include central–local government relations, systems of local government finance and the role of the courts. Both traditions of study were represented at the LSE: the former in a longrunning course called Comparative Local Government, taught by George Jones; the latter in Urban Politics, convened by Patrick Dunleavy. With Jones and Dunleavy away, Keith Dowding and I created the hybrid.